Impetuous Youngsters and Jaded Old-Timers: Acquiring a Reputation for Learning - Prendergast, Canice; Stole, Lars (Journal of Political Economy, 1996)
This paper examines individual decision making when decisions reflect on people's ability to learn. The authors address this problem in the context of a manager making investment decisions on a project over time. They show that, in an effort to appear as a fast learner, the manager will exaggerate his own information but ultimately he becomes too conservative, being unwilling to change his investments on the basis of new information. The authors' results arise purely from learning about competence rather than concavity or convexity of the rewards functions. They relate their results to the existing psychology literature concerning cognitive dissonance reduction. Copyright 1996 by University of Chicago Press.